Language barriers in pediatric food allergy care: A single-center study on healthcare disparities - Katelyn H. Wong; Nishant Pandya; Sarah McCollum; Veronika Shabanova; Gary K. Soffer (PLoS ONE, 2026)
Background There is limited knowledge of healthcare utilization and food allergy outcomes among non-primary English-speaking patients in the United States, despite language barriers potentially being a risk factor for less optimal health outcomes. Methods A retrospective cohort study was conducted of patients 0−18 years old with food allergy seen at our institution’s allergy and immunology clinic between 1/1/2018-12/31/2021. Only patients with food allergy, defined as prior history of symptoms consistent with IgE-mediated reaction to food(s) and positive skin prick testing (wheal ≥ 3 mm) or food-specific IgE > 0.35, were included. Demographics and clinical data were obtained from the electronic health record (EHR). Regression analyses examined the association between patient/guardian-reported primary language and healthcare utilization, and whether COVID-19 pandemic modified these associations. Results Of the 1,418 patients with food allergy identified, 1,267 were primary English speakers and 151 were non-primary English speakers. Non-primary English-speaking patients had lower odds of EHR portal activation as compared to primary-English speakers (52.3% vs 81.8%, adjusted odds ratio = 0.43, 95% confidence interval (CI) 0.29–0.62). Regarding non-primary English-speakers, an increase in the probability of EHR portal activation (from 61.6% [95% CI 51.5% − 71.8%] to 70.0% [95% CI 60.8%−78.7%]) and food-related emergency department visits (from 3.7% [95% CI −0.4%−7.9%] to 19.4% [95% CI 10.7%−28.0%]) from the pre-COVID-19 to COVID-19 period was noted. Conclusion Disparities in rates of EHR portal activation and emergency department utilization which were differentially affected by the COVID-19 pandemic were identified among non-primary English-speaking patients in a cohort of pediatric patients with food allergy at a tertiary care referral center in the United States. This study highlights the need for greater understanding of language-based health disparities in food allergy and for more equitable EHR portal access among non-primary English-speaking patients.